Does higher degree of monopoly imply worse results for output and employment? - Alejandro Rodríguez Arana (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2007)
In an economy producing n symmetric goods (where n is an integer number equal or greater than one), monopolistic competition produces smaller output and employment than perfect competition. The inferiority of the equilibrium is directly related to the number of goods produced and to the returns of labour on production (when there is just one good perfect competition and monopoly are equivalent). Therefore, inter-industry coalitions among monopolistic competitors approach the economy to the perfect competition equilibrium. In the limit, when all monopolistic competitors collude, the ex ante recognition of symmetries implies an identical equilibrium than perfect competition.